2021
DOI: 10.3390/su13179941
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Distribution and Modeling of the Impact of Women Driving Cars on the Sustainable Development of Saudi Arabia

Abstract: Background: This work investigated attitudes and public perception regarding the impact of allowing women to drive on social, environmental, and economic aspects of the sustainable development in the Kingdom of Saudi Arabia (KSA). The study includes the perspectives of both women and men towards the potential implications of this decree on society in general and women’s well-being in particular. Methods: The methodology consisted of an online survey that was conducted before and after the decree was activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(28 reference statements)
0
0
1
Order By: Relevance
“…Consistent with our study, no gender differences were reported. The absence of gender differences may reflect the gender equity push that has been inserted in all sectors of Saudi Arabia, including education, by the 2030 Vision [81][82][83]. However, in our study, students' beliefs did not seem to correspond much to their actions (as per correlation analyses).…”
Section: Discussioncontrasting
confidence: 74%
“…Consistent with our study, no gender differences were reported. The absence of gender differences may reflect the gender equity push that has been inserted in all sectors of Saudi Arabia, including education, by the 2030 Vision [81][82][83]. However, in our study, students' beliefs did not seem to correspond much to their actions (as per correlation analyses).…”
Section: Discussioncontrasting
confidence: 74%